Strategi Pembentukan Bi’ah Lughawiyah Maharah Al-Kalam Bahasa Arab di MA Mu’allimin Nahdlatul Wathan Pancor - Mugni; Baiq Raudatussolihah (LP3M Sekolah Tinggi Agama Islam Nahdlatul Wathan SAMAWA SUMBAWA BESAR, 2022)
Strategy of formation of biah lughawiyah maharah Arabic in Madrsah Aliyah Mu’allimin Nahdlatul Wathan Pancor, East Lombok. This study aims to determine the problematic of biah lughawiyah maharah al-kalam Arabic in Madrsah Aliyah Mu’allimin Nahdlatul Wathan Pancor, East Lombok. This research is aqualitative research, data collection was done by observing this research obtained through research instrument in for stages. Namely data reduction, data analysis, display data in the results showed that the problematic of the student are more muted in learningnahwu and sharaf, embarrassed and rigid in speaking, worried about making mistakes,afraid of making mistakes cricitism, lack of motivation and participation from for the madrasa senate, more focus on studying the rules and a more in-depeth study of the book of furats, the absence of friends to speak Arabic,putting forward passive language (maharah al-istima’ and al-qra maharah’ah). The strategy for the formation of bi’ah lughawiyah maharah al-kalam language Arabic thatresearchers offer is to form Arabic-speaking groups that are not tied to the place, wherever they are, they should speak Arabic even if being wrong in using the rules of nahwu and sharaf